Intertextual Awareness in EFL Report Writing: Comparing Students’ Use of Field-Based and Web-Based Sources - Tedi Rohadi; Hendi Hidayat; Herawati Fajrin (STIT Buntet Pesantren Cirebon, 2025)
This qualitative study investigates how EFL students engage with field-based and web-based sources in academic report writing, focusing on their intertextual strategies of selection, interpretation, and integration. Data were collected from 32 third-semester students through reflective questionnaires, semi-structured interviews, and student report texts. Guided by Bazerman’s intertextual typology and Canagarajah’s translingual framework, thematic analysis revealed two distinct but overlapping intertextual repertoires. Field-based engagement fostered experiential curiosity, dialogic interpretation, and narrative integration rooted in cultural immediacy. In contrast, web-based engagement promoted algorithmic search behaviour, multimodal decoding, and citation-driven structuring. While both modes demonstrated strategic meaning-making, field-based practices reflected stronger authorial voice and epistemic agency. The findings suggest that pedagogical support should cultivate both embodied inquiry and digital literacy to enhance students’ critical intertextual competence. Implications are offered for integrating hybrid source use into academic writing instruction and for future research on adaptive authorship in EFL contexts.